The surface microstructure of cusps and leaflets in rabbit and mouse heart valves - Ye, Xia; Bhushan, Bharat; Zhou, Ming; Lei, Weining (Beilstein Journal of Nanotechnology, 2014)
In this investigation, scanning electron microscopy was used to characterize the microstructure on the surfaces of animal heart valve cusps/leaflets. The results showed that though these surfaces appear smooth to the naked eye, they are actually comprised of a double hierarchical structure consisting of a cobblestone-like microstructure and nano-cilia along with mastoids with a directional arrangement. Such nanostructures could play a very important role in the hemocompatibility characteristics of heart valves. On this basis, the model of the microstructure was constructed and theoretical analysis was used to obtain optimal geometric parameters for the rough surface of artificial valve cusps/leaflets. This model may help improve reconstructive techniques and it may be beneficial in the design and fabrication of valve substitutes or partial substitutes. Namely, the model may help ameliorate heart valve replacement surgery.
Keywords: contact angle; geometric parameter; heart valve; hemocompatibility; microstructure